2017
DOI: 10.1080/19425120.2017.1360419
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Ecological Monitoring to Individual Marine Reserves: Comparing Longline to Hook‐and‐Line Gear to Monitor Fish Species

Abstract: Fishery-independent hook-and-line surveys are currently being used to assess marine reserve performance in California and Oregon using a regionally standardized approach. Catch compositions generated from these hookand-line surveys (pole-and-line gear) at Oregon's southernmost marine reserve were compared with local commercial landing data. Several species present in the commercial catch were undersampled in the marine reserve hook-and-line dataset, including China Rockfish Sebastes nebulosus, Vermilion Rockfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…). The results also underscore the need to tailor monitoring techniques to individual marine protected areas and their unique management needs (Huntington and Watson ).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…). The results also underscore the need to tailor monitoring techniques to individual marine protected areas and their unique management needs (Huntington and Watson ).…”
Section: Resultsmentioning
confidence: 85%
“…Such complimentary sampling would essentially promote an ecosystem-based approach to fisheries management, where the focus of research and management policies aiming to control levels of fishing pressure becomes the ecosystem rather than an individual target species (Cappo et al 2004;Pikitch et al 2004;Watson et al 2005;Frid et al 2006;Lowry et al 2012). The results also underscore the need to tailor monitoring techniques to individual marine protected areas and their unique management needs (Huntington and Watson 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, using standardized sampling methods over a 5-year period, we found significant variation in year-to-year trends in reef fish abundance in the eastern Gulf of Mexico, and some of these data have already been used in stock assessments (Christiansen et al 2017(Christiansen et al , 2018(Christiansen et al , 2019SEDAR 2019). As in the present study, a few active hooked-gear surveys have been able to maintain a longer time series of standardized collections and to track annual abundance trends for Lingcod (Yamanaka and Murie 1995;, rockfish species (Harms et al 2010;Huntington and Watson 2017), and Tautog (Vidal et al 2018). Further research with the RTD method should explore seasonal trends in catch to inform and improve the overall sampling design.…”
Section: Model Variablementioning
confidence: 78%
“…Many countries have been carrying out various conservation and management programs, such as marine protected areas or marine reserves, to help recover marine and coastal fisheries (Meyer et al 2007;Chateau and Wantiez 2009;Lester et al 2009). Determining and understanding the distribution patterns and habitat characteristics of ecologically or economically important marine species are fundamental steps for the design and management of marine protected areas (Pearce et al 2001;Huntington and Watson 2017;Sala and Giakoumi 2018). Examining the seasonal distribution and spatial connectivity of species populations in marine protected areas can help provide a better understanding of migration and spawning movements of focal species, especially fishery species, and further improve the spillover effects of marine protected areas (Russ 2002;Choat 2012).…”
mentioning
confidence: 99%